Vientos para el cambio. Territorios, energía eólica y cooperativas de electricidad en el sur bonaerense - Jacinto, Guillermina Paula (2014)
The availability of electric energy is a strategic factor for the socio-productive development, and energy infrastructure grids are a backbone of economic and territorial system integration. The existence of large distances between the centers of production and the centers of processing and consumption, along with the inability to store electricity, makes it necessary to develop a technique that ensures the circulation linking transportation systems with the points where users require electricity. This work presents the electric distribution cooperatives in the Province of Buenos Aires as central links of the distribution process at the local and regional scale. Also, in a context of decentralized production incentives, we explore new scenarios and challenges to cooperatives, posed by the possibilities opened by projects of generation from wind sources in the provincial south.